ANALISIS HUKUM TENTANG WEWENANG MAJELIS PENGAWAS DAERAH PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 49/PUU-X/2012 - SILVIA SUMBOGO (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Muhd Yamin, SH, MS,CN2.  Prof. Dr. Budiman Ginting, SH, MHum3.  Dr. T. Keizerina Devi A, SH, CN, MHum The Ruling of the Constitutional Court No.49/PUU-X/2012 has revoked one of the authorities of the Regional Supervision Council as it is stipulated in Article 66, paragraph 1 of Law No.30/2004 which give approval to investigators, public prosecutors, or judges in the interest of judicial administration to take the copy of the minute of the deed and/or any letter attached to the Minute of the Deed or the Notarial Protocol from the Notarial deposit and call on the Notary to be present in the examination related to the deed he has made and to the Notarial Protocol in the Notarial Deposit. The result of the research showed that after the Rulling of the Constitutional Court No.49/PUU-X/2012 was enacted, Notary still has other types of legal protection such as right of objection, obligation to objection and Notarial Honor Council. The Ruling of the Constitutional Court No.49/PUU-X/2012 does not directly imply Notary in doing his job; he only ascertains the intention/wish the parties concerned in the form of a deed according to the prevailing legal provisions although he has to be very careful in issuing any deed, and his other authorities have to be in line with the prevailing legal provisions and with Notarial Code of Ethics.Keywords: Regional Supervision Council